Carbon Nanodots as Electrocatalysts towards the Oxygen Reduction Reaction. Issue 3 (2nd January 2018) - Martínez‐Periñán, Emiliano; Bravo, Iria; Rowley‐Neale, Samuel J.; Lorenzo, Encarnación; Banks, Craig E.
Abstract: Electrocatalysts perform a key role in increasing efficiency of the oxygen reduction reaction (ORR) and as a result, efforts have been made by the scientific community to develop novel and cheap materials that have the capability to exhibit low ORR overpotentials and allow the reaction to occur via a 4 electron pathway, thereby mimicking as close as possible to traditionally utilised platinum. In that context, two different types of carbon nanodots (CNDs) with amide (CND‐CONH2 ) and carboxylic (CND‐COOH) surface groups, have herein been fabricated and shown to exhibit excellent electrocatalytic activity towards the ORR in acid and basic media (0.1 M H2 SO4 and 0.1 M KOH). CND surface modified carbon screen‐printed electrodes allow for a facile electrode modification and enabling the study of the CNDs electrocatalytic activity towards the ORR. CND‐COOH modified SPEs are found to exhibit improved ORR peak current and reduced overpotential by 21.9 % and 26.3 %, respectively compared to bare/unmodified SPEs. Additionally, 424 μg cm −2 CND‐COOH modified SPEs in oxygenated 0.1 M KOH are found to facilitate the ORR via a near optimal 4 (3.8) electron ORR pathway. The CNDs also exhibited excellent long‐term stability and tolerance with no degradation being observed in the achievable current with the ORR current returning to the baseline level within 100 seconds of exposure to a 1.5 M solution of methanol. In summary, the CND‐COOH could be utilised as a cathodic electrode for PEMFCs offering greater stability than a commercial Pt electrode. Abstract :